CXCL16 Stimulates Antigen-Induced MAIT Cell Accumulation but Trafficking During Lung Infection Is CXCR6-Independent - Yu, Huifeng; Yang, Amy; Liu, Ligong; Mak, Jeffrey Y. W.; Fairlie, David P.; Cowley, Siobhan (Frontiers in Immunology, 2020)
Mucosa-associated invariant T (MAIT) cells are a unique T cell subset that contributes to protective immunity against microbial pathogens, but little is known about the role of chemokines in recruiting MAIT cells to the site of infection. Pulmonary infection with Francisella tularensis live vaccine strain (LVS) stimulates the accrual of large numbers of MAIT cells in the lungs of mice. Using this infection model, we find that MAIT cells are predominantly CXCR6+ but do not require CXCR6 for accumulation in the lungs. However, CXCR6 does contribute to long-term retention of MAIT cells in the airway lumen after clearance of the infection. We also find that MAIT cells are not recruited from secondary lymphoid organs and largely proliferated in situ in the lungs after infection. Nevertheless, the only known ligand for CXCR6, CXCL16, is sufficient to drive MAIT cell accumulation in the lungs in the absence of infection when administered in combination with the MAIT cell antigen 5-OP-RU. Overall, this new data advance the understanding of mechanisms that facilitate MAIT cell accumulation and retention in the lungs.